Analysis of Job Stress and Burnout Syndrome on nurses in Emergency Unit During Covid-19 Pandemic Studied at East Java Region - Mufarika Mufarika; Zuryaty Zuryaty (Universitas STRADA Indonesia, 2021)
Burnout Syndrome is a acumulation of destructive physical, psychological and mental symptoms occuring from monotonous and stressful work fatigue. The purpose of this study was to analyze job stress and burnout syndrome on nurses in the emergency department during the covid-19 pandemic. The method used analytical survey with a cross sectional approach. The sampling technique is simple random sampling, the statistical test used Sperman Rank test with (0.05). The research instrument used the Maslach Burnout Inventory and depression anxiety stress scales (DASS 42) using Google forms. The results of the Spearman Rank statistical test obtained p value 0.000 < (0.05) where it can be concluded that there is a relationship between job stress and burnout syndrome on nurses who work in the Emergency Unit Around Hospitals atl East Java. Efforts to minimize burnout syndrome includes increasing emotional intelligence, individual coping, spirituality, relationships with coworkers, and improving aspects of nurse leadership